IMPLEMENTASI KEGIATAN PENCAMPURAN WARNA UNTUK MEMBENTUK KETERAMPILAN SAINS DI TK NEGERI PEMBINA BUNGORO - Ashar (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2020)
Abstract: Implementation of Color Mixing Activities in Shaping the Simple Science Skills of the Bungoro State Trustees. This research aims to form science skills through the implementation of color mixing activities in the Bungoro State Development Kindergarten. Classroom action research. Subjects in the study were 21 students and 2 teachers. Data collection techniques are observation and interview. Analysis of the data used descriptive analysis. The results of observations in the first cycle conducted on students with indicators of conducting science experiments by doing the activity of mixing the basic colors of red + blue + yellow. Of the 21 students observed there were 7 students in the very well developed category (BSB). In the category of developing according to expectations (BSH) there are 3 students, In the category of developing (MB) there are 5 students, while undeveloped (BB) there are categories of 6 students. The results of the second cycle observations conducted on students with indicators of conducting science experiments by doing the activity of mixing the basic colors of red + blue + yellow. Of the 21 students observed there were 9 students in the very well developed category (BSB). In the category of developing according to expectations (BSH) there are 8 students, In the category of developing (MB) there are 3 students, while undeveloped (BB) there are categories of 1 students.